Wide-Area Damping Controller Design Based on the Frequency Domain Self-Excitation Method - Lei Gao; Yanchao Ma; Yonghui Nie; Shiyun Xu; Xiaojie Chu; Long Peng (Journal of Control Science and Engineering)
In this paper, a wide-area DC damping controller design method is proposed to damp the weak interarea oscillation modes. First, the low-order power system control model identification method is proposed based on the frequency domain self-excitation method to obtain the dominant modes and other related information. In what follows, the identified model is transformed into a low-order state space equation. By comparing the geometric metrics of different schemes, the various input signals and installation locations of the controller are selected. Furthermore, the damping controller parameter calculation is realized based on the self-excitation frequency domain identification method, which does not depend on the detailed model of the system. The design process is simple and it is easy to apply in the practical engineering of large-scale complex power grids. The applicability and effectiveness of the proposed controller design method are demonstrated through simulations of a two-area four-generator power system.